Financial statements not required - Minnis, Michael; Sutherland, Andrew G.; Vetter, Felix W. (Journal of Accounting and Economics, 2024)
Using a dataset covering 3 million commercial borrower financial statements, we document a substantial, nearly monotonic decline in banks’ use of attested financial statements (AFS) in lending over the past two decades. Two market forces help explain this trend. First, technological advances provide lenders with access to a growing array of borrower information sources that can substitute for AFS. Second, banks are increasingly competing with nonbank lenders that rely less on AFS in screening and monitoring. Our results illustrate how technology adoption and changes in credit market structure can render AFS less efficient than alternative information sources for screening and monitoring.